Studi Unjuk Kerja Pembangkit Listrik Tenaga Uap (PLTU) Air Anyir Bangka - Wahri Sunanda (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2019)
Air Anyir Bangka Steam Power Plant (PLTU) as a back bone generator in Bangka, Considering that the growth of load every year in the Air Anyir Bangka power plant continues to increase, the value of efficiency in the power sector must be considered in order to support the quality of the generating system and services to the community. The purpose of this study is to analyze the efficiency of turbines and generators before and after overhaul and determine the maximum efficiency of the load using the enthalphi reduction method. The results of the analysis are obtained after overhauling the efficiency of turbines and generators is better and the efficiency of the load varies which shows the efficiency increases